A implementação de uma política reversa ou circular como condição de efetividade do direito para exigibilidade e validade da cobrança da taxa de lixo pelos municípios - Maciel, Alexandre Dias (2024)
The central objective of this research is the implementation of a reverse or circular policy for the proper disposal of solid waste, considered essential for the effectiveness of the provision of the public garbage collection service. This implementation is analyzed as an indispensable condition for the enforceability and validity of the collection of garbage fees by municipalities. The problem of the research that it proposes to investigate is the following: “Which provisions of Law No. 12,305/2010 are not being complied with by the municipalities, what are the consequences of this non-compliance and why is this legislation not effectively implemented, considering its essentiality in configuring the requirement of the service effectively provided or made available for the purpose of collecting a garbage fee or ecotax?” The answers to these questions were extracted from research conducted in the municipalities of Suzano, Arujá, Ferraz de Vasconcelos and Poá (located in AltoTietê and belonging to the Metropolitan Region of the State of São Paulo) and are included in the Annexes of this work. As can be seen from the studies, although these municipalities have drawn up their own municipal solid waste plans, as determined by article 18 of Federal Law No. 12,305/2010, none of them have effectively complied with their own solid waste plans and are far from effectively complying with Federal Law No. 12,305/2010, considering that the deadline for this obligation was August 2024. As can be inferred from the Annexes, the municipalities responded to eleven questions related to compliance with Federal Law No. 12,305/2010, and none of them stated that they were fully complying with the aforementioned law. The justifications, for the most part, focus on the lack of financial resources, the absence of infrastructure and the recognition that the fees charged are insufficient to cover the costs necessary for the implementation of a true reverse or circular policy. Two of the municipalities acknowledged that they cannot charge the fee if the municipality is not able to comply with the National Solid Waste Policy in its entirety, which corroborates this thesis. The reverse or circular policy provided for in Law No. 12,305/2010 is absolutely necessary to ensure the effectiveness of the Solid Waste Law. The return of waste to the production chain, through recycling or reuse, not only contributes to reducing the volume of waste sent to landfills, but also represents a relevant environmental policy, since it is public knowledge that irregular disposal of solid waste contaminates rivers, forests and seas, not to mention that the return of solid waste to the production chain will represent a defense of mineral reserves. This process directly contributes to the preservation of natural resources, by reducing the need to exploit virgin raw materials, promoting a more sustainable cycle of use that is less dependent on mineral extraction. This research shows that most municipalities are not complying with the national solid waste policy as established by Federal Law 12.305/2010. The collection of garbage fees as established by Binding Precedent No. 19 of the Federal Supreme Court (STF) will not meet the requirements of 'public service rendered or made available', as determined by article 145, item II, of the Federal Constitution and article 77 of the National Tax Code, as long as the municipalities do not provide services in accordance with the provisions of Law No. 12.305/2010. The municipalities of Suzano and Arujá stated that they have suspended their collections to adapt the amounts to the needs of the PNRS, while Ferraz de Vasconcelos and Poá stated that their collections do not meet 20% of the amounts necessary to fund a solid waste policy as established by the PNRS. The inevitable conclusion reveals non-compliance and the need to establish sanctioning mechanisms for the municipalities themselves, until the implementation of the national solid waste policy along the lines of law 12.305/2010